USING THE LEARNING OF RECIPROCAL TEACHING BASED ON OPEN ENDED TO IMPROVE MATHEMATICAL CRITICAL THINKING ABILITY - Widodo Winarso; Putri Hardyanti (Jurusan Tadris Matematika UIN Siber Syekh Nurjati Cirebon, 2019)
This study aims to determine the application of reciprocal teaching approach assisted by open-ended problem questions which have implications in improving the mathematical critical thinking skills of students in class VII of Â SMPN 1 Weru Cirebon. This type of research is true experimental research in a randomized pretest-posttest control group design. The instruments used in this study were questionnaires and tests of students' mathematical critical thinking skills. The data analysis technique used is descriptive statistics and inferential statistical analysis with the F test (One Way ANOVA). Based on the results of the descriptive analysis, the responses of the experimental class 1 students> the response of the experimental class 2 students (76.94> 73.42), the results of the improvement in students' critical thinking skills obtained by the experimental class Gain value 1> experiment 2> control (0.65> 0 , 56> 0.48). Based on the inferential analysis, obtained Fcount > Ftable (25,213> 5,34) and Sig value <0,05, then H0 is rejected, meaning there are significant differences between the three classes. Furthermore, the Tukey's HSD test was obtained that the mean difference value of the experimental class 1> experiment 2> control. Then it can be concluded that the application of the reciprocal teaching model assisted with the open-ended problem has implications in improving the mathematical critical thinking skills of the students